In-situ electrochemical modification method for surface structure of lithium-rich manganese-based oxide
By generating dense spinel phases on the surface of lithium-rich manganese-based oxide positive electrode material, the problem of poor cycling performance of the material at high voltage is solved, and the electrochemical performance and capacity retention of the material are improved.
Patent Information
- Application Number
- CN202411741836.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-15
Smart Images

Figure CN119822423A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material surface treatment, and in particular to an in-situ electrochemical modification method for the surface structure of lithium-rich manganese-based oxides. Background Art
[0002] In recent years, the market scale of new energy vehicles has been continuously expanding, and higher requirements for the cruising range have also been put forward. The lithium-rich manganese-based oxide cathode material has a structure of xLi2MnO3·(1-x)LiMO2 (0 < x < 1, M = Ni, Co, Mn) and has a specific capacity of more than 300 mAh / g, which has great potential for solving the current "range anxiety" problem. However, this material still has problems such as poor cycling performance and voltage decay, which limit its further commercialization.
[0003] Since the high capacity of the lithium-rich manganese-based oxide (LRMO) cathode material needs to be activated at a relatively high charging voltage, and the side reactions on the material surface will be more serious under a high-voltage system. In response to this, researchers have carried out a large number of modification studies, and the modification methods focus on surface coating, surface treatment, etc. However, most of the methods are complex in operation, high in cost, and most surface modifications will reduce the capacity of the material. Electrochemically, the activation degree of the lithium-rich manganese-based oxide or the formation of the CEI film is usually controlled by controlling the charging cut-off voltage. For example, Chinese Patent Application CN114784398A and Chinese Patent CN107959071B do not specifically change the surface structure of the material. Chinese Patent CN115784313B uses the method of controlling the charging cut-off voltage to generate a rock salt phase with a thickness of 2-10 nm on the surface of the lithium-rich manganese-based material, and its voltage range is generally 2.0-4.8V. However, the formation of the rock salt phase will reduce the specific capacity of the material, and at the same time, the change of the charging cut-off voltage also has a greater impact on the electrolyte. Summary of the Invention
[0004] In order to overcome the deficiency in the in-situ stabilization technology of the surface structure of the existing lithium-rich manganese-based oxide material, where a rock salt phase is generated on the surface of the lithium-rich manganese-based material, resulting in a reduction in the specific capacity of the material, the present invention provides an in-situ electrochemical modification method for the surface structure of lithium-rich manganese-based oxides. After the activated material is deeply lithiated below 2.0 V at an appropriate rate, a uniform and dense spinel phase is formed on its surface by controlling the lithiation depth and the lithiation rate, effectively improving the cycling performance of the material and improving the electrochemical performance of the material without reducing the capacity of the lithium-rich manganese-based oxide material and without significantly oxidizing the electrolyte.
[0005] In a first aspect, a method for in-situ electrochemical modification of the surface structure of a lithium-rich manganese-based oxide is provided, comprising: assembling a lithium-rich manganese-based battery using the lithium-rich manganese-based oxide, activating the battery, and performing a first discharge on the activated lithium-rich manganese-based battery at a rate of 0.1C-0.5C, wherein the cut-off voltage of the first discharge is ≤2.0 V, and the cut-off voltage of the first discharge is maintained for constant voltage discharge for 0.1-12 h; the first discharge is performed at least once.
[0006] Ternary materials such as NCA can embed excessive lithium below 3 V, and the surface will be transformed into a 1T phase (space group P3m1) of Li2MO2 composition. Irreversible phase changes occur on the surface of the material, which gradually reduce the performance and life of NCA. The formation of the 1T phase is due to the excessive lithium embedding in the tetrahedral position, which leads to the crystal plane slip of the layered structure. In the lithium-rich manganese-based oxide positive electrode material, Mn will migrate to the lithium layer after reduction and gradually transform into a spinel phase, which may hinder the slip of the crystal plane to a certain extent, making it difficult to generate a 1T phase. The surface structure can still maintain the O3 phase consistent with the bulk structure. At the same time, due to the excessive embedding of lithium, it can also hinder the further migration of Mn and prevent the formation of a rock salt phase that does not have electrochemical activity. Therefore, the method of the present invention can controllably form a spinel phase on the surface of the material in situ. The surface spinel phase can increase the diffusion rate of lithium ions on the one hand, and on the other hand, it can also hinder the precipitation of O in the bulk structure and the oxidation reaction with the electrolyte, thereby improving the electrochemical performance of the material.
[0007] In some implementations, the cut-off voltage of the first discharge is 1.2V-1.5V.
[0008] In some implementations, the current rate of the first discharge is 0.1C-0.2C.
[0009] In some embodiments, the first discharge maintains a constant voltage discharge at the cut-off voltage for 0.5-1 h.
[0010] By controlling the cut-off voltage, current rate and constant voltage discharge time of the first discharge within the above range, the spinel phase can be better formed on the surface of the material, thereby improving the electrochemical performance of the material without reducing the capacity of the lithium-rich manganese-based oxide material and without oxidizing the electrolyte in large quantities.
[0011] In some embodiments, the first discharge is performed 1-3 times. Controlling the number of the first discharge to 1-3 times can better form a spinel phase on the surface of the material, thereby improving the electrochemical performance of the material without reducing the capacity of the lithium-rich manganese-based oxide material and without oxidizing the electrolyte in large quantities. Wherein, when the number of times exceeds 1, the cut-off voltage for charging after the discharge is ≥4.0V.
[0012] In some embodiments, after the first discharge, a second charge and a second discharge are further included. Preferably, the cut-off voltage of the second charge is ≥4.0 V, and the current rate of the second charge is 0.1-3C. Preferably, the cut-off voltage of the second discharge is ≤1.8 V, and the current rate of the second discharge is 0.1-0.5C; the cut-off voltage of the second discharge is maintained for constant voltage discharge for 0.1-12h.
[0013] After the first discharge is completed, the second charge and the second discharge are performed, which has the effect of strengthening the first charge and discharge action.
[0014] In some embodiments, the activated lithium-rich manganese-based oxide is cycled 1-3 times in the order of the first discharge, the second charge, the second discharge, and the second charge. The specific sequence is cycled 1-3 times to further activate the material and enhance the effect of the surface modification of the material.
[0015] In some embodiments, the activation cutoff voltage is ≥4.45V.
[0016] In some embodiments, a battery is assembled using a lithium-rich manganese-based oxide material as a positive electrode and a lithium sheet or lithium foil as a negative electrode, and an electrochemical activation treatment is performed.
[0017] In some embodiments, the lithium-rich manganese-based oxide is selected from Li a Mn b Ni c Co d O2, where 1<a≤1.5, 0.3≤b≤0.7, 0.1≤c≤0.5, 0.01≤d≤0.3.
[0018] In some embodiments, the lithium-rich manganese-based oxide is selected from Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2、Li 1.12 Mn 0.45 Ni 0.35 Co 0.01 O2、Li 1.25 Mn 0.54 Ni 0.13 Co 0.01 At least one of O2.
[0019] In a second aspect, a positive electrode plate is provided, which is a lithium-rich manganese-based oxide obtained by the aforementioned modification method.
[0020] In a third aspect, a battery is provided, which uses the lithium-rich manganese-based oxide and / or the positive electrode sheet obtained by the above-mentioned modification method. Wherein "battery" refers to a battery cell, a battery module or a battery pack.
[0021] In a fourth aspect, an electric device is provided, which uses the battery. The battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto. As the electric device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0022] As an example, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0023] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0024] The in-situ electrochemical modification method of the surface structure of lithium-rich manganese-based oxide provided by the present invention can controllably form a dense spinel phase on the surface of the material in situ by controlling the cut-off voltage, current rate and constant voltage discharge time during the discharge process, thereby improving the electrochemical performance of the material in situ without losing the battery capacity.
[0025] The in-situ electrochemical modification method for the surface structure of the lithium-rich manganese-based oxide provided by the present invention is simple and easy to operate, can achieve better electrochemical performance of the lithium-rich manganese-based oxide positive electrode material, improve the capacity retention rate of the lithium-rich manganese-based oxide material (battery) and reduce voltage decay, and the method of controlling low voltage has little effect on the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is one of the TEM spectra of the modified lithium-rich manganese-based oxide material and the FFT transformation diagram of the corresponding area in Example 1 of the in-situ electrochemical modification method of the surface structure of the lithium-rich manganese-based oxide material provided by the present invention.
[0028] Figure 2One of the first cycle charge and discharge curves of Example 1 (dashed line) and Comparative Example 1 (solid line) of the in-situ electrochemical modification method for the surface structure of the lithium-rich manganese-based oxide material provided by the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In some embodiments, the cut-off voltage of the first discharge is ≤2.0V, such as 1.2-1.5V, the current rate is 0.1-0.2C, and the constant voltage discharge time is 0.1-12h, such as 0.5-1h.
[0031] In some embodiments, the cut-off voltage of the second discharge is ≤1.8V, such as 1.2-1.5V, the current rate is 0.1-0.5C, such as 0.1-0.2C, and the constant voltage discharge time is 0.1-12h, such as 0.5-1h.
[0032] In the embodiments, when the battery is cycled, the cycle voltage is 2.0-4.8V, such as 2.0V, 2.5V, 3.0V, 3.5V, 4.0V, 4.5V and 4.8V and the like and the voltage range thereof, unless otherwise specified, and a cycle voltage of 2.0V is used in the embodiments; the cycle current ratio is between 0.1-3C, such as 0.1C, 1C, 2C, 3C and the like and the current ratio range thereof, unless otherwise specified, and a cycle current ratio of 1C is used in the embodiments.
[0033] In the embodiment, one cycle refers to completing a complete charge and discharge process, and a complete charge and discharge process includes discharging the battery from a fully charged state to 0%, and then charging it to a fully charged state.
[0034] In the embodiment, the negative electrode of the battery is a lithium sheet or lithium foil. In other embodiments, when the negative electrode is graphite, silicon-based or other materials, the cut-off voltage of the first discharge, the cut-off voltage of the second charge and the cut-off voltage of the second discharge are changed accordingly to adapt to the matching between the positive and negative electrodes. Those skilled in the art can convert them according to common knowledge. For example, when the voltage range for lithium is 2-4.5V, the voltage range for graphite is 1.5-4.55V, and so on.
[0035] In the embodiment, the first charge-discharge and the second charge-discharge conditions are the same, the charge cut-off voltage is 5V, and the charge current rate is 0.1C.
[0036] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially. In each embodiment and comparative example, the lithium-rich manganese-based oxide positive electrode material, electrolyte and lithium sheet negative electrode are assembled according to a method well known in the art to obtain a lithium-ion battery.
[0037] Example 1 This embodiment provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, comprising: (1) Preparation of lithium-rich manganese-based positive electrode: 2g of Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2 is an active particle, 5g of PVDF glue with a solid content of 5% and 0.25g of conductive agent carbon black are dispersed in 3g of NMP to prepare a slurry; the slurry is coated on the current collector and dried to obtain a positive electrode sheet, and the dried electrode sheet is cut into a disc with a diameter of 14mm, and then vacuum dried; (2) Battery assembly: In an argon atmosphere glove box (Mbraun UNIlab max), the vacuum-dried disc, a 16 mm diameter separator (Celgard 2400), and a 16 mm diameter lithium sheet were assembled in sequence, and then 1 mL of electrolyte (1 M LiPF6 dissolved in EC\DMC solvent) was dripped to prepare a CR2032 type button battery; (3) subjecting the button battery to electrochemical activation treatment: charging the button battery with a cut-off voltage ≥ 4.45 V; (4) After being fully charged, the button battery is discharged at a rate of 0.1C, the voltage is reduced to 1.5V (i.e., the cut-off voltage is 1.5V), and maintained for 0.5h to generate a spinel phase on its surface.
[0038] In this embodiment, the CR2032 button battery obtained in step (2) was used to perform a charge and discharge test at a constant temperature of 25° C. at a rate of 0.1C, and the initial specific capacity was 250 mAh / g.
[0039] Example 2 This embodiment provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is basically the same as that of Embodiment 1, except that in step (4), after being fully charged, the voltage is reduced to 1.2 V at a rate of 0.2C and maintained for 1 h.
[0040] Example 3 This embodiment provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is basically the same as that of embodiment 1, except that: 1.12 Mn 0.45 Ni 0.35 Co 0.01 The O2 material was prepared into electrode sheets and assembled into CR2032 button batteries. At a constant temperature of 25°C, a preliminary charge and discharge test was carried out at a rate of 0.1C, and the initial specific capacity was 230mAh / g. After being fully charged, the voltage was reduced to 1.2V at a rate of 0.1C and maintained for 0.5h to generate a spinel phase on the surface of the material.
[0041] Example 4 This embodiment provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is basically the same as that of embodiment 1, except that: 1.12 Mn 0.45 Ni 0.35 Co 0.01 The O2 material was prepared into an electrode sheet and assembled into a CR2032 button cell. A preliminary charge and discharge test was carried out at a constant temperature of 25°C at a rate of 0.1C, and the initial specific capacity was 230 mAh / g. After being fully charged, the voltage was reduced to 1.5 V at a rate of 0.1C for 1 hour to generate a spinel phase on the surface of the material.
[0042] Example 5 This embodiment provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is basically the same as that of embodiment 1, except that: 1.25 Mn 0.54 Ni 0.13 Co 0.01 The O2 material was prepared into electrode sheets and assembled into CR2032 button batteries. At a constant temperature of 25°C, a preliminary charge and discharge test was carried out at a rate of 0.2C, and the initial specific capacity was 280mAh / g. After being fully charged, the voltage was reduced to 1.2 V at a rate of 0.1C and maintained for 0.5h to generate a spinel phase on the surface of the material.
[0043] Example 6 This embodiment provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is basically the same as that of embodiment 1, except that: 1.25 Mn 0.54 Ni 0.13 Co 0.01The O2 material was prepared into an electrode sheet and assembled into a CR2032 button cell. A preliminary charge and discharge test was carried out at a constant temperature of 25°C at a rate of 0.2C, and the initial specific capacity was 270 mAh / g. After being fully charged, the voltage was reduced to 1.5 V at a rate of 0.1C and maintained for 1 hour to generate a spinel phase on the surface of the material.
[0044] Comparative Example 1 This comparative example provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is basically the same as Example 1, except that the discharge cut-off voltage during the in-situ electrochemical treatment is uniformly 2.0 V.
[0045] Comparative Example 2 The present comparative example provides an in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide material, which is different from Example 1 in that: the in-situ modification method of Example 1 in CN 115784313B is adopted: the battery is transferred to 55°C and allowed to stand for 10 hours, and 0.05C current rate is used at 55°C for 15 cycles in the range of 4.5 to 2.0V to complete the activation cycle process (with the anion capacity no longer increasing as the node), and can be used for subsequent working cycles of 500 times at 4.8V to 2V at a current rate of 1C.
[0046] Test Example 1 Battery Specific Capacity Retention and Voltage Decay Test object: the modified lithium-rich manganese-based battery in each embodiment and comparative example and cycled 500 times (also referred to as 500 weeks).
[0047] Test method: (1) Specific capacity retention rate: The specific capacity after 500 cycles at a current rate of 1C divided by the specific capacity at the third cycle.
[0048] (2) Voltage decay: The difference between the discharge voltage at the third cycle and the 500th cycle at a current rate of 1C is divided by the number of cycles (500) to obtain the average weekly voltage decay, which is recorded as weekly voltage decay.
[0049] Test results: The specific capacity retention rate and voltage decay results of the modified lithium-rich manganese-based oxide materials in each embodiment and comparative example after 500 cycles are shown in Table 1.
[0050] Table 1
[0051] It can be seen from Table 1 that the lithium-rich manganese-based battery treated by the in-situ electrochemical modification method of the surface structure of the lithium-rich manganese-based oxide provided by the present invention has a higher capacity retention rate. Figure 1The TEM image in the figure shows that the in-situ electrochemical modification method of the surface structure of the lithium-rich manganese-based oxide provided by the present invention forms dense spinel on the surface of the lithium-rich manganese-based oxide. The lithium-rich manganese-based battery treated by the in-situ electrochemical modification method of the surface structure of the lithium-rich manganese-based oxide provided by the present invention has a lower voltage decay, indicating that the method of the present invention improves the structural stability of the material surface during the cycle and reduces the erosion of the electrolyte on the material surface.
[0052] By comparing Example 1 with Comparative Example 1, the present application significantly improves the specific capacity retention rate of the battery and significantly reduces the cycle voltage decay by optimizing the discharge cut-off voltage in the in-situ electrochemical modification method, indicating that the cycle stability and voltage decay of the battery treated by the modification method of the present application are significantly improved.
[0053] Comparing Examples 1-6 and Comparative Example 2, compared with the battery treated by the modification method provided in Comparative Example 2, the battery treated by the modification method of the present application has a higher specific capacity retention rate and significantly less cyclic voltage attenuation, indicating that the modification method provided by the present application is significantly more effective than the prior art.
[0054] Test Example 2 TEM analysis Test object: the lithium-rich manganese-based oxide that has been in-situ electrochemically modified in Example 1.
[0055] Experimental method: Samples were taken from the surface of the lithium-rich manganese-based oxide that had been in situ electrochemically modified in Example 1, and a FEI Tecnai G2 F20 transmission electron microscope (TEM) was used for scanning analysis (the test voltage was 200 kV), and FFT transformation was performed on the corresponding area to observe whether a spinel phase was formed on the surface of the lithium-rich manganese-based oxide.
[0056] Test results: TEM lens results and FFT transformation of the corresponding area are as follows Figure 1 shown.
[0057] from Figure 1 It can be seen that when the surface of the surface-modified lithium-rich manganese-based oxide is subjected to TEM lens, it can be seen that the bulk phase of the treated positive electrode material still maintains a good layered structure (solid line frame), and a layer of spinel phase (dashed line frame) is generated on the surface.
[0058] Test Example 3: First Week Charge and Discharge Test Test object: lithium-rich manganese-based oxides subjected to in-situ electrochemical modification in Example 1 and Comparative Example 1.
[0059] Test method: The battery was charged and discharged at a current rate of 0.1C, with voltage ranges of 2.0-4.8V and 1.5-4.8V respectively.
[0060] Test results: The first week of charge and discharge test results are as follows Figure 2 shown.
[0061] from Figure 2 It can be seen that Example 1 can still release part of its capacity below 2.0V, a new voltage platform and phase change appear, and the discharge specific capacity can reach more than 350mAh / g; while the button battery in Comparative Example 1 stops discharging at around 2.0V, and the discharge specific capacity is about 250mAh / g.
[0062] comprehensive Figure 1 and Figure 2 It can be seen that the scheme shown in the embodiment of the present invention can effectively improve the electrochemical performance of lithium-rich manganese-based oxide positive electrode materials. The present invention provides an innovative in-situ electrochemical modification method for the surface structure of lithium-rich manganese-based oxides. By controlling the electrochemical treatment conditions, the in-situ formation of the spinel phase on the surface of the material is achieved; after 500 cycles, the capacity retention rate and voltage decay of the lithium-rich manganese-based oxide (battery) indicate that the in-situ electrochemical modification provided by the present invention significantly improves the electrochemical performance and cycle stability of the lithium-rich manganese-based oxide material (battery); the lithium-rich manganese-based oxide that forms a spinel phase on the surface after in-situ electrochemical modification has broad market application prospects and scientific research value.
[0063] For example, the modified lithium-rich manganese-based oxide material is further applied to the positive electrode to obtain a lithium-rich manganese-based positive electrode plate, a battery using the lithium-rich manganese-based positive electrode plate, and an electrical device using the battery. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. As the electrical device, a battery cell, a battery module, or a battery pack can be selected according to its usage requirements.
[0064] As an example, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0065] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An in-situ electrochemical modification method for the surface structure of a lithium-rich manganese-based oxide, characterized in that: include: The lithium-rich manganese-based oxide is used to assemble a lithium-rich manganese-based battery, which is activated. The activated lithium-rich manganese-based battery is subjected to a first discharge at a rate of 0.1C-0.5C, wherein the cut-off voltage of the first discharge is ≤2.0 V, and the cut-off voltage of the first discharge is maintained for constant voltage discharge for 0.1-12 hours; the first discharge is performed at least once.
2. The modification method according to claim 1, characterized in that The cut-off voltage of the first discharge is 1.2V-1.5V; And / or, the current rate of the first discharge is 0.1C-0.2C; And / or, the first discharge maintains a constant voltage discharge at the cut-off voltage for 0.5-1 h.
3. The modification method according to claim 1 or 2, characterized in that The first discharge is performed 1-3 times.
4. The modification method according to any one of claims 1 to 3, characterized in that After the first discharge, it also includes a second charge and a second discharge; Preferably, the cut-off voltage of the second charge is ≥4.0 V, and the current rate of the second charge is 0.1-3C; Preferably, the cut-off voltage of the second discharge is ≤1.8 V, and the current rate of the second discharge is 0.1-0.5C; the cut-off voltage of the second discharge is maintained for constant voltage discharge for 0.1-12 hours.
5. The modification method according to any one of claims 1 to 4, characterized in that: The activated lithium-rich manganese-based battery is cycled 1-3 times in the order of the first discharge, the second charge, the second discharge and the second charge.
6. The modification method according to any one of claims 1 to 5, characterized in that: The activation cut-off voltage is ≥4.45V.
7. The modification method according to any one of claims 1 to 6, characterized in that: Assembling a battery using a lithium-rich manganese-based oxide material as a positive electrode and a lithium sheet or lithium foil as a negative electrode, and performing an electrochemical activation treatment; Preferably, the lithium-rich manganese-based oxide is selected from Li a Mn b Ni c Co d O2, where 1<a≤1.5, 0.3≤b≤0.7, 0.1≤c≤0.5, 0.01≤d≤0.3; Preferably, the lithium-rich manganese-based oxide is selected from Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2、Li 1.12 Mn 0.45 Ni 0.35 Co 0.01 O2、Li 1.25 Mn 0.54 Ni 0.13 Co 0.01 At least one of O2, etc.
8. A positive electrode sheet, characterized in that: The lithium-rich manganese-based oxide is obtained by treatment with the modification method according to any one of claims 1 to 7.
9. A battery, characterized in that: The lithium-rich manganese-based oxide and / or the positive electrode sheet according to claim 8 are obtained by treatment with the modification method according to any one of claims 1 to 7.
10. An electrical device, characterized in that: The battery according to claim 9 is used.
Citation Information
Patent Citations
A lithium-ion battery and its formation method
CN107959071B
Method for improving electrochemical performance of lithium-rich manganese-based lithium ion battery
CN114784398A
In-situ surface modification method of lithium-rich manganese-based layered positive electrode material
CN115784313B